2019
DOI: 10.1155/2019/8204129
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Amazonian Fruits: A Mini Review of In Vivo and In Vitro Studies

Abstract: Brazil, Colombia, Ecuador, Peru, Bolivia, Venezuela, Suriname, Guyana, and French Guiana share an area of 7,295,710 km2 of the Amazon region. It is estimated that the Amazonian forest offers the greatest flora and fauna biodiversity on the planet and on its surface could cohabit 50% of the total existing living species; according to some botanists, it would contain about 16-20% of the species that exist today. This region has native fruit trees in which functional properties are reported as antioxidant and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 59 publications
0
20
0
4
Order By: Relevance
“…In the Colombian Amazon, as well as in the Brazilian and Peruvian Amazon, camu-camu [Myrciaria dubia (Kunth) McVaugh] is a promising non-timber forest product because it is a natural source of vitamin C and other compounds relevant to human health PINHEIRO, 2018;AVILA-SOSA et al, 2019). Thanks to these properties, it is a product with increasing demand in national and international markets (PROMPERU, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the Colombian Amazon, as well as in the Brazilian and Peruvian Amazon, camu-camu [Myrciaria dubia (Kunth) McVaugh] is a promising non-timber forest product because it is a natural source of vitamin C and other compounds relevant to human health PINHEIRO, 2018;AVILA-SOSA et al, 2019). Thanks to these properties, it is a product with increasing demand in national and international markets (PROMPERU, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Hu D. et al [6] have found an inverse association with pear consumption in a meta-analysis that includes evidences from prospective cohort studies about the association of fruits and vegetable consumption with the risk of stroke. The compounds of the greatest interest for their antioxidant and functional properties include phenolic compounds, unsaturated fatty acids, carotenoids, phytosterols, and tocopherols as well as flavonoids [7]. The pear, one of the oldest crops by humans [8], represents an important source of biologically active substances and is largely consumed worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with marine ecosystems, the richest sources of bioactive compounds in terrestrial ecosystems are found in habitats with high complexity and biodiversity such as mangroves or rainforests (Zhou & Guo, 2012; Cândido, Silva & Agostini‐Costa, 2015; Avila‐Sosa et al, 2019). However, a great many of these habitats are severely affected by climate change, and this together with a lack of national or international regulations on human activity in these areas puts the species inhabiting them under extreme threat (Osorio, Wingfield & Roux, 2016; de Oliveira Roque et al, 2018), particularly animal species used in traditional medicine.…”
Section: Discussionmentioning
confidence: 99%